Haploinsufficiency of the mouse Tshz3 gene leads to kidney defects. Issue 12 (17th December 2021) - Sanchez-Martin, Irene; Magalhães, Pedro; Ranjzad, Parisa; Fatmi, Ahmed; Richard, Fabrice; Manh, Thien Phong Vu; Saurin, Andrew J; Feuillet, Guylène; Denis, Colette; Woolf, Adrian S; Schanstra, Joost P; Zürbig, Petra; et al.
Abstract: Renal tract defects and autism spectrum disorder (ASD) deficits represent the phenotypic core of the 19q12 deletion syndrome caused by the loss of one copy of the TSHZ3 gene. Although a proportion of Tshz3 heterozygous ( Tshz3 +/lacZ ) mice display ureteral defects, no kidney defects have been reported in these mice. The purpose of this study was to characterize the expression of Tshz3 in adult kidney as well as the renal consequences of embryonic haploinsufficiency of Tshz3 by analyzing the morphology and function of Tshz3 heterozygous adult kidney. Here, we described Tshz3 expression in the smooth muscle and stromal cells lining the renal pelvis, the papilla and glomerular endothelial cells (GEnCs) of the adult kidney as well as in the proximal nephron tubules in neonatal mice. Histological analysis showed that Tshz3 +/lacZ adult kidney had an average of 29% fewer glomeruli than wild-type kidney. Transmission electron microscopy of Tshz3 +/lacZ glomeruli revealed a reduced thickness of the glomerular basement membrane and a larger foot process width. Compared to wild type, Tshz3 +/lacZ mice showed lower blood urea, phosphates, magnesium and potassium at 2 months of age. At the molecular level, transcriptome analysis identified differentially expressed genes related to inflammatory processes in Tshz3 +/lacZ compare to wild-type (control) adult kidneys. Lastly, analysis of the urinary peptidome revealed 33 peptides associated with Tshz3 +/lacZ adult mice. These results provide the first evidence that in the mouse Tshz3 haploinsufficiency leads to cellular, molecular and functional abnormalities in the adult mouse kidney.